COMPETITIVENESS OF THE FISHERY SECTOR IN LATVIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The aim of the research is to evaluate the competitiveness of Fishery Sector in Latvia. Based on the author developed Model of the Factors influencing Competitiveness of the Fisheries Sector Cluster and methodology of the Index of Fishery Sector Competitiveness the authors determined the competitiveness level of Fishery Sector in Latvia and identified spheres influencing competitiveness: facilitating and promising spheres as well as procrastinatory and stagnating spheres, moreover the possibilities of further development were established. The author has developed the evaluation methodology of the Fishery Sector Competitiveness that can be used in any country in the Fishery Sector for the evaluation of competitiveness. The elaborated methodology for evaluation of competitiveness may assist the institutions involved in the Fisheries' policy formation to work more successfully and improve the common policy in the Fisheries sector.